An analysis of soccer referee experiences in France and the Netherlands: Abuse, conflict, and level of support. Issue 1 (February 2020) - Webb, Tom; Dicks, Matt; Thelwell, Richard; van der Kamp, John; Rix-Lievre, Géraldine
Highlights: This research considers referee abuse and support across two European countries. Intergroup conflict and conflict resolution as theoretical concepts were utilized. Extends our knowledge of referee and match official abuse in sport. Referees require greater support from governing bodies in both countries. Conflict resolution is required between referees, players, coaches and spectators. Abstract: Referee and match official discontinuation in sport is an issue of relevance to sport managers and administrators. Despite this, it is an often-neglected area of sport management research. In this paper, a critical analysis of the discontinuation of soccer referees across two countries is provided, utilizing an intergroup conflict theoretical construct to frame the analysis, drawing on the concept of conflict resolution to consider solutions to the issues uncovered. The distribution and subsequent analysis of an online survey in both France and the Netherlands facilitated engagement with a total of 4, 637 referees, comprising 3, 408 from France and 1, 229 from the Netherlands. Following the thematic analysis higher order themes related to aggression, abuse and support systems emerged. Referees reported that verbal abuse was a frequent occurrence, and that incidents of physical abuse were also evident, indicating a culture of abuse toward referees in both countries. Referees as an outgroup felt marginalized, as players, coaches and spectators form ingroups with shared objectives. Additional findings suggest that the support structures around the referees require strengthening at both local and national level, to address issues related to discontinuation. The authors conclude by discussing the implications of the research on the match official abuse related literature, as well as identifying suggestions for researchers and practitioners.